Association Between Regulatory Emotional Self-Efficacy and Immunosuppressive Medication Adherence in Renal Transplant Recipients:Does Medication Belief Act as a Mediator? - Jia Liu; Jia Liu; Jia Liu; Xiao Zhu; Xiao Zhu; Jin Yan; Jin Yan; Jin Yan; Lina Gong; Xiaoxia Wu; Min Liu; Min Liu; et al. (Frontiers Media S.A., 2021)
Background: Few studies have investigated the association between regulatory emotional self-efficacy (RESE) and immunosuppressive medication adherence or the mechanisms underlying this relationship. Considering that previous evidence of immunosuppressive medication adherence depended on the level of immunosuppressive medication beliefs, a model of multiple mediation was tested in which immunosuppressive medication beliefs acted as mediators of the relationship between RESE and immunosuppressive medication adherence.Methods: A retrospective cross-sectional study was performed in 293 renal transplant patients during outpatient follow-ups from November 2019 to February 2020 in China. All participants completed a general demographic questionnaire, the Chinese version of the RESE, the Beliefs about Medication Questionnaire, and the Basel Assessment of Adherence with Immunosuppressive Medication Scale (BAASIS). Spearson correlation analysis was carried out to identify the correlation between RESE and immunosuppressive medication adherence. Binary logistic regression analysis was performed to confirm factors associated with immunosuppressive medication adherence in renal transplant recipients. Mediating effect analysis was used to explore the internal interaction between RESE and immunosuppressive medication adherence.Results: A total of 293 renal transplant patients were recruited, including 111 women and 182 men with a mean age of 42.5 years (SD = 10.0). A total of 23.21% of patients exhibited immunosuppressive medication none-adherence behavior, and 12.97% reported altering the prescribed amount of immunosuppressive medication without physician permission, which was most popular behavior among patients. The mean RESE score was 45.78 ± 6.12; the positive (POS) score was the highest, and the anger-irritation (ANG) score was the lowest. The correlation analysis results showed that RESE (r = −0.642, p < 0.01) and immunosuppressive medication beliefs (r = −0.534, p < 0.01) were significantly associated with immunosuppressive medication adherence. Binary logistic regression analysis indicated that marital status, fertility status, rejection, immunosuppressive medication beliefs, and RESE were found to be independent predictors of immunosuppressive medication adherence [R2 = 0.803, p < 0.05]. The results of the mediating effect analysis showed that immunosuppressive medication necessity had a partial mediating effect, RESE directly and indirectly affected immunosuppressive medication adherence via immunosuppressive medication necessity, and immunosuppressive medication concerns were not a mediator between RESE and immunosuppressive medication adherence.Conclusion: The levels of immunosuppressive medication adherence in renal transplant patients need to be improved in China. Marital status, fertility status, rejection, immunosuppressive medication beliefs, and RESE were major factors affecting immunosuppressive medication adherence. RESE could affect immunosuppressive medication adherence indirectly through immunosuppressive medication necessity.